Inovasi Pembelajaran PAI Berbasis Student Centered Learning Pada Generasi Alpha - Hafizh Raafi; Ahmad Saifulloh; Ilman Hafidzul Huda; Akmal Najemi; Haiqal Kahfi (MA'ALIM: Jurnal Pendidikan Islam, 2026)
The rapid development of digital technology has transformed learning patterns among Generation Alpha, who are highly familiar with digital media and interactive learning environments. This condition encourages the need for innovative approaches in Islamic Religious Education (PAI), particularly through Student Centered Learning (SCL). This study aims to analyze the implementation, challenges, and implications of SCL based PAI learning for Generation Alpha in the digital era. The research employed a qualitative approach using library research methods. Data were collected through documentation techniques from books, scientific journals, and relevant academic sources, then analyzed using content analysis. The findings indicate that SCL based PAI learning, supported by digital media, gamification, collaborative learning, and project-based learning, can improve students’ motivation, participation, critical thinking, and religious character development. However, challenges remain in teachers’ digital competence, technological facilities, and students’ digital distractions. In conclusion, SCL based PAI learning is an adaptive and effective approach for supporting 21st-century Islamic education.